Гуньдытӥсь нянь: повестьёс / Николай Куликов - Куликов Николай Васильевич (Удмуртия, 1991)
Экземпляры: (20240409) / Инвентарный номер: 21906 / Цена: 10.40 / Сис.шифр: 84(2=664.1) / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2=664.1)